Meta-analysis of correlationship between HLA-G 3′UTR 14-bp Ins/Del polymorphism and virus susceptibility. Issue 38 (September 2018) - Lv, Haiyan; Lv, Huizhi; Lin, Zhong; Chen, Lihua; Zhu, Min; Hong, Dun
Abstract: Background: There is a considerable amount of literature on the potential relationship between human leukocyte antigen-G 14-bp Ins/Del polymorphism and virus infection; however, results from these studies were inconclusive. Objectives: A meta-analysis was carried out to determine whether the 14-bp Ins/Del polymorphism is a susceptible factor for virus infection. Methods: Data were extracted from PubMed and Web of Science databases, and included 10 case–control studies (1835 patients and 2357 controls). Results: A total of 177 records from 10 studies were retrieved. Overall, no significant correlation was found between HLA-G 14-bp Ins/Del polymorphism and total viruses under all genetic models (dominant model: OR = 0.93, 95% CI = 0.68–1.29; recessive model: OR = 1.12, 95% CI = 0.84–1.48; deletion/deletion (DD) vs insertion/insertion (II): OR = 1.03, 95% CI = 0.71–1.49; deletion (D) vs insertion (I): OR = 1.01, 95% CI = 0.81–1.25). However, further subgroup analyses by virus type and ethnicity revealed that HLA-G 14-bp Ins/Del polymorphism was significantly associated with HTLV-1 infection in mixed population under the dominant model. Conclusions: Our study demonstrated that HLA-G 14-bp Ins/Del polymorphism may not have any effect on susceptibility to viruses.